Can Writing Anxiety Change Over Time? Evidence from a Mixed-Method Study - Ni'mah, Dzurriyyatun; Kurniasih, Kurniasih; Hidayanti, Ika; Nadzri, Fazyudi Ahmad (FKIP Universitas Lampung, 2026)
Researching the role of psychology in language learning is interesting because of its significant impact, particularly on emotion, which is believed to be at the heart of language learning. Some theories of language learning acquisition believe that anxiety is a situation-specific psychological aspect that may remain stable in any learning situation. This study delves into the difference in writing anxiety over time (within 2022-2025). A total of 33 EFL students have fully participated in this study since 2022 (at the beginning of their study) until their final year (2025). Adopting a mixed-methods design, the quantitative data were obtained from the SLWAI Questionnaire developed by Cheng (2004), and the qualitative data were collected through interviews with selected students whose anxiety remained stable, increased, or decreased over the course of their study. The interviews were conducted face-to-face, guided by interview guidelines that could be further developed based on participants' responses. The findings revealed significant differences in writing anxiety from 2022 to 2025. However, the level remains stable over time, which means that students have a high level of anxiety with different mean scores. The mean score was 74.36 (high) in 2022, 71.82 (high) in 2023, and 69.03 (high) in 2025. The students have explained various factors causing changes in anxiety over time, including a shift in focus from speaking to writing, international academic endeavors, adequate background knowledge of writing topics, and factors related to teachers and peers. This study encourages writing teachers to implement anxiety-reducing strategies to alleviate students’ writing anxiety. Suggestions for further research are also provided. Keywords: writing anxiety, EFL students, longitudinal study, qualitative.